2012
DOI: 10.3315/jdcr.2012.1109
|View full text |Cite
|
Sign up to set email alerts
|

Sézary syndrome, Kaposi sarcoma and generalized dermatophytosis 15 years after sulfur mustard gas exposure

Abstract: Background:The relationship between compromised immune system and the development of malignancy, generalized dermatitis, and infection after sulfur mustard gas exposure has been established. Main observation:We introduce a 58-year-old man with an abrupt, de novo and erythrodermic eruption in 2002 that was previously exposed to sulfur mustard during the Iran -Iraq war in 1987. Six weeks after the onset of diffuse eruption, he developed papules on the glans penis and generalized dermatophytosis. A biopsy of his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Finally Emadi et al . reported a 58‐year‐old veteran with Sézary syndrome, Kaposi sarcoma and generalized dermatophytosis 15 years after short‐term exposure to SM …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally Emadi et al . reported a 58‐year‐old veteran with Sézary syndrome, Kaposi sarcoma and generalized dermatophytosis 15 years after short‐term exposure to SM …”
Section: Discussionmentioning
confidence: 99%
“…Finally Emadi et al reported a 58-year-old veteran with S ezary syndrome, Kaposi sarcoma and generalized dermatophytosis 15 years after short-term exposure to SM. 27 In spite of several limitations of this report including retrospective design, lack of comparison with unexposed subjects during the study period and unknown pathophysiology of MF development, our unique series can build a platform for other researchers to investigate the carcinogenicity impact of single exposure to SM. We also suggest molecular analysis such as TCR gene rearrangement or microRNA studies to probably help to differentiate early cutaneous T-cell lymphoma (CTCL) from other inflammatory skin disorders like dermatitis in those exposed to SM.…”
Section: Discussionmentioning
confidence: 99%
“…In Sardasht-Iran cohort study, it has been shown that (79.9%) of the Iranian SM-exposed individuals suffer from chronic skin disorders [2]. The most common nonsignificant chronic skin complications were xerosis, eczema, seborrheic dermatitis, cherry angioma, hyperpigmentation, urticaria, and vitiligo while mustard scar was the most significant finding among chemical victims in Sardasht City [2,3,14].…”
Section: P1: Comparison Of the Serum Level Of No Between Participantsmentioning
confidence: 99%
“…SM exposure leads to short-and long-term adverse effects on body organs, especially the skin, eyes, respiratory tract, and immune system [2]. The most common SMinduced chronic skin complications are mustard scars, xerosis, eczema, seborrheic dermatitis, cherry angioma, hyperpigmentation, and some rare skin cancers [2][3][4][5]. Despite various studies on the long-term clinical manifestations of skin toxicity in SM-exposed individuals, the pathogenesis of SM-induced skin disorders needs more investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Research in humans showed that, 20 years after the SM exposure, the severely affected victims of the Iran-Iraq war had a lower CD3 + CD4 + level and higher CD3 + CD8 + level in plasma compared to normal controls [ 13 ]. Another study in humans, found that 15 years after sulfur mustard gas exposure, participants had Sezary syndrome and increased CD3 + CD4 + /CD3 + CD8 + cells in flow cytometry [ 14 ]. Other studies observed increased percentages of CD3 + CD4 + and CD3 + CD8 + T cells in tissues and body fluids in hairless guinea pigs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%